Reactive Risk-Taking: Anxiety Regulation Via Approach Motivation Increases Risk-Taking Behavior. (January 2023) - Leota, Josh; Nash, Kyle; McGregor, Ian
Experimental research and real-world events demonstrate a puzzling phenomenon—anxiety, which primarily inspires caution, sometimes precedes bouts of risk-taking. We conducted three studies to test whether this phenomenon is due to the regulation of anxiety via reactive approach motivation (RAM), which leaves people less sensitive to negative outcomes and thus more likely to take risks. In Study 1 ( N = 231), an achievement anxiety threat caused increased risk-taking on the Behavioral Analogue Risk Task (BART) among trait approach-motivated participants. Using electroencephalogram in Study 2 ( N = 97), an economic anxiety threat increased behavioral inhibition system-specific theta activity, a neural correlate of anxiety, which was associated with an increase in risk-taking on the BART among trait approach-motivated participants. In a preregistered Study 3 ( N = 432), we replicated the findings of Study 1. These results offer preliminary support for the reactive risk-taking hypothesis.